Structural Studies of Liquids and Glasses Using Aerodynamic Levitation - Farmer, Thomas (Springer, 2016)
This thesis presents neutron scattering data that contribute to the understanding of four distinct areas of condensed matter physics, including iso-compositional liquid-liquid phase transitions and the glass formation in rare earth doped BaTi2O5.